Fundamentals of database management system - Padre, Nilo M. (Intramuros, Manila, Philippines : Unlimited Books Library Services and Publishing Inc., 2017)
Fundamentals of database management system (DBMS) is written to provide you with the basic understanding in the ways database is managed in order to address the increasing demand of the industry, society, and the community.
CHAPTER 1 Database management concepts -- CHAPTER 2 Database design (table structure) -- CHAPTER 3 Normalization -- CHAPTER 4 Relationship -- CHAPTER 5 Quey-by example -- CHAPTER 6 SQL (structured query language).
Includes bibliographical references.
Keywords: DATABASE SYSTEM